EXPLORING THE POLITICS OF LOCAL PARTICIPATION IN RURAL DEVELOPMENT PROJECTS: SMALL DAMS REHABILITATION PROJECT IN ZIMBABWE - Jacob Tagarirofa; Bernard Chazovachii (Russian Journal of Agricultural and Socio-Economic Sciences, 2013)
The study sought to evaluate the effectiveness of community participation in rural development projects in Zimbabwe testing the credibility of the popularized supposition that almost all contemporary development efforts characteristically embrace local participation. Public participation is widely assumed to be an essential ingredient for the fruition of rural development efforts. The research made use of quantitative and qualitative research methodologies in which unstructured interviews, focus group discussions and questionnaires were used as data gathering instruments. The analysis of data was enabled by the use of People-Centered Development (PCD) as a conceptual framework. Findings revealed that the level of community participation in the district is not only minimal, but it is also top down. This has much to do with the negative perceptions by facilitating agents viewing local people as passive recipients of externally crafted models of development and other factors such as the power dynamics within and between the community and other stakeholders. The research also found preferential treatment of other tribal groups by the facilitating agent, intra group conflicts and bureaucratic and political influence as obstacles militating against effective participation. Based on these findings, and consistent with the wider literature, recommendation are that the nature of community engagement should be based on the principle of equal partnership among all stakeholders as this would encourage full cooperation and thus effective participation.